Digital Storytelling: How Canva Helps Students Build Visual and Written Narratives - Reva Angelina; Ester Monica Bu’ulolo; Rita Hartati (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aims to explore students’ perceptions of using Canva as a digital storytelling platform to enhance their visual and written narrative skills in English writing. The research employed a descriptive qualitative method involving 34 students who participated in a questionnaire consisting of eight closed-ended statements and two open-ended questions. The data were analyzed descriptively, using percentages to support qualitative interpretation. The findings revealed that most students perceived Canva as an accessible, enjoyable, and effective tool for developing writing skills. Students agreed that Canva helps them visualize ideas, organize stories logically, and combine words with images creatively. Moreover, Canva was found to improve students’ motivation, confidence, and emotional expression in English writing. These results are consistent with previous studies by Utami and Suriyani (2022), Febriansyah et al. (2023), Siregar et al. (2024), Herwani (2024), Eragamreddy and Joseph (2025), Hafidzin et al. (2025), and Jayanti et al. (2025), which collectively highlight Canva’s role in supporting writing engagement, creativity, and organization. The study concludes that Canva transforms traditional writing into a multimodal and meaningful process, combining linguistic and visual literacy. Therefore, Canva can be considered an innovative pedagogical tool that promotes creative thinking, digital competence, and expressive communication in the English writing classroom.